High-Containment Agriculture Animal Research: An AAALAC International Perspective. (19th April 2021) - Harper, Susan B; Bayne, Kathryn; Anderson, Kenneth E
Abstract: Institutions that conduct high-containment agricultural research involving domestic livestock represent a specialized category of programs that are accredited by AAALAC International. The accreditation process includes a comprehensive assessment of the overall program of animal care and use. However, the complex design of these facilities and the unique care required for animals in this type of environment often mean that additional attention will be directed at areas regarded as higher risk when the programs are evaluated. Specific issues that may stimulate additional discussion and interest include animal housing practices, environmental conditions inside the facility, maintenance of procedure and support areas, methods for obtaining and safely transporting healthy research animals, strategies to minimize animal pain and distress, unusual protocol review challenges, and institutional policies relevant to personnel training and safety. These issues are further discussed to inform institutions of potential concerns that should be reviewed and assessed during internal preparations for accreditation visits by AAALAC site visit teams.